Keberlakuan Peraturan Pemerintah Yang Belum Ada Peraturan Pelaksanaannya - Ismail, Alferin Salsabilla; Az Zahra, Qaisya; Pratiwi Nurcahyan, Eka; Nurul Anisa, Adelia (AL WASATH Jurnal Ilmu Hukum, 2024)
Regarding the PP delegating detailed rules into its implementing regulations, it indicates that the PP and its implementing regulations become one unit that makes the law clear and enforceable. It is possible that the implementation regulations have not yet been enforced to affect the validity of Government regulations, but they could affect the effectiveness of a PP’s work. This paper aims to discuss the applicability of Goverment regulation for which implementing regulations do not yet exist or cannot yet apply. There are a number of Goverment regulation whose implementing regulations were not enforced immediately, raising the question: how are these PP’s enforced and what are the implications, whether they will affect their effectiveness or not. This study uses the method of literature study or documentary study to conclude that PP’s whose implementing regulations have not been enforced do not hinder the enforcement of the Goverment regulation , but may affect the technical performance of these Goverment regulation.